1986
DOI: 10.1159/000116089
|View full text |Cite
|
Sign up to set email alerts
|

Light Treatment in Depressive Illness

Abstract: Objective and subjective quality of sleep and awakening as well as circadian rhythms in Cortisol, temperature and well-being were investigated in 10 female hospitalized depressed patients diagnosed as major depressive disorders according to RDC criteria before (baseline), during (intervention) and after (recovery) treatment with biologically active or bright light (BL) and were compared with the findings in 10 normals. Polysomnographic evaluation demonstrated in depressed patients an increased sleep latency, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Elevated body temperature at night, a time when thermoregulatory cooling responses are important for sleep onset and sleep quality (Raymann et al, 2005 , 2008 ; Romeijn et al, 2011 ), is the most consistently observed circadian abnormality in depression (Avery et al, 1982b ; Souetre et al, 1988 ; Duncan, 1996 ), an abnormality that typically normalizes with clinical improvement, (e.g., following ECT, antidepressant drug treatment or spontaneous recovery) (Avery et al, 1982a , b ). Although not observed in all studies, a phase advance in the 24-h pattern of body temperature has also been described in some depressed patients (Dietzel et al, 1986 ; Goetze and Tolle, 1987 ; Souetre et al, 1988 ; Parry et al, 1989 ). Interestingly, despite the higher nocturnal temperature in depressed patients, there is no concomitant increase in nighttime sweating (Avery et al, 1999 ).…”
Section: Evidence Linking Thermosensation With Affective States Relevmentioning
confidence: 85%
“…Elevated body temperature at night, a time when thermoregulatory cooling responses are important for sleep onset and sleep quality (Raymann et al, 2005 , 2008 ; Romeijn et al, 2011 ), is the most consistently observed circadian abnormality in depression (Avery et al, 1982b ; Souetre et al, 1988 ; Duncan, 1996 ), an abnormality that typically normalizes with clinical improvement, (e.g., following ECT, antidepressant drug treatment or spontaneous recovery) (Avery et al, 1982a , b ). Although not observed in all studies, a phase advance in the 24-h pattern of body temperature has also been described in some depressed patients (Dietzel et al, 1986 ; Goetze and Tolle, 1987 ; Souetre et al, 1988 ; Parry et al, 1989 ). Interestingly, despite the higher nocturnal temperature in depressed patients, there is no concomitant increase in nighttime sweating (Avery et al, 1999 ).…”
Section: Evidence Linking Thermosensation With Affective States Relevmentioning
confidence: 85%
“…Although the hypothesis of a circadian phase disturbance underlying depression is discussed in most of the literature, a controlled study of light exposure with the purpose of shifting circadian rhythms in nonseasonal depressives hardly ever is carried out. Either light is given both in the morning and in the evening (Dietzel et al, 1986;Peter, 1986;Kripke et al, 1987Kripke et al, , 1992 or light exposure at other sensitive phases of the biological clock is not avoided (Deltito et al, 1991;Bauer, 1993;Thalén et al, 1995). Obviously, both approaches are inadequate to induce systematic shifts in circadian rhythms.…”
Section: Introductionmentioning
confidence: 99%
“…The action of light is not confined to seasonal affective disorder (SAD); bright light attenuates depressive symptoms in non-SAD patients. However, the effects are minimal and controversial (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%